2021
DOI: 10.1186/s12879-021-06514-9
|View full text |Cite
|
Sign up to set email alerts
|

“OPTIONS-DC”, a feasible discharge planning conference to expand infection treatment options for people with substance use disorder

Abstract: Background Serious bacterial infections associated with substance use often result in long hospitalizations, premature discharges, and high costs. Out-of-hospital treatment options in people with substance use disorder (SUD) are often limited. Methods We describe a novel multidisciplinary and interprofessional care conference, “OPTIONS-DC,” to identify treatment options agreeable to both patients and providers using the frameworks of harm reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…While this might seem curious, it is because, despite leaving against medical advice, these participants remained reachable, often providing reliable contact information and agreeing to follow up before leaving the medical facility. Further, the involvement of a dedicated, interprofessional team focused on co-management of substance use disorder and infections aided discharge discussions, similar to that proposed by other models ( 34 ). In contrast, preintervention patients were left without similar options, and many who did discharge against the medical team's advice did so in a less coordinated way, often remaining unreachable or, when reached, declining to discuss their stay.…”
Section: Discussionmentioning
confidence: 99%
“…While this might seem curious, it is because, despite leaving against medical advice, these participants remained reachable, often providing reliable contact information and agreeing to follow up before leaving the medical facility. Further, the involvement of a dedicated, interprofessional team focused on co-management of substance use disorder and infections aided discharge discussions, similar to that proposed by other models ( 34 ). In contrast, preintervention patients were left without similar options, and many who did discharge against the medical team's advice did so in a less coordinated way, often remaining unreachable or, when reached, declining to discuss their stay.…”
Section: Discussionmentioning
confidence: 99%
“…OPTIONS-DC, a multidisciplinary and interprofessional care conference developed at Oregon Health & Science University, works under harm reduction and patient-centered models to identify treatment options which are acceptable to both patients and HCPs, and investigators demonstrated that it is entirely feasible to integrate practices of harm reduction into treatment for patients who need long-term antibiotic treatment. 29 Other studies have shown that hospital-based harm reduction promotes patient-centered care. 30 In our study, many participants emphasized harm reduction principles and the importance of prioritizing the needs and preferences of PWUD, even when those preferences are against what HCPs believe to be the best treatment course for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive and collaborative clinical care and coordination by dedicated, expert teams, in the style of tumor boards, can ameliorate some of the challenges of the fragmented health and social support systems. 29 …”
Section: Discussionmentioning
confidence: 99%